The Attributive Structure as a Predicate in Light of Modern Linguistic Approaches - Alhejoj, Mohammad Abdel Rahman Hasan (Dirasat: Human and Social Sciences, 2025)
Objectives: This study addresses the attributive structure of the sentence, starting from its meaning in deep structure and reaching its structure in surface form through the connection of sentence structure with the subject. The aim is to understand the opinions of ancient grammarians and discuss them in light of contemporary linguistic approaches. Method: The study adopted a descriptive-analytical approach as a tool to examine the treatment of ancient grammarians of examples of attributive sentence structures and analyze them. Since this analysis relies on data from contemporary linguistic studies, it utilized the generative-transformational approach, the functional approach, and functional lexicogrammatical theory. Results: The study revealed that the nominal sentence structures, whose predicate is an attributive structure, are transformed structures from deep structures that the language resorts to for purposes dictated by discourse context and the speaker’s intention. Conclusion: The study concluded that the connections in nominal structures whose predicate is an attributive structure are constructed by the language to establish relationships between structure elements, ensuring coherence and avoiding the idea of separation. Thus, they are interconnected and semantically and structurally cohesive structures.